GAME KIDSAFE SOLUSI EDUKATIF UNTUK MENGENALKAN PENDIDIKAN SEKSUAL PADA ANAK USIA DINI 4-5 TAHUN - Fadillah, Sahria; Iriyanto, Tomas; Maningtyas, Rosyi Damayani Twinsari (Dharmas Education Journal (DE_Journal), 2024)
Sexual violence that occurs in early childhood has increased in recent years. The lack of learning media in introducing sexual education is one of the problems that need to be overcome. The purpose of this research is to create a KidSafe Game to introduce sexual education for 4-5 years old children that is effective, efficient and interesting by not limiting the resources of its users. In this study, researchers used a design (research and development) by adapting the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The results through the trial showed a significant difference in understanding from early childhood between before and after being given the KidSafe Game. The result of expert validation in terms of effectiveness, efficiency, and attractiveness obtained a percentage of 96% material expert and 97% media expert.